Pengaruh Inkuiri Terbimbing Terhadap Hasil Belajar Siswa Kelas IV di MI Nurul Falah Karangpuri - Lutfianah, Nur Laili; Wulandari, Fitria (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This study aims to determine the effect of guided inquiry model on learning outcomes of fourth grade students of MI Nurul Falah Karangpuri. This research includes pre-experimental design with one group pretest and postest design. The population in this study were all fourth grade students of MI Nurul Falah Karangpuri, totaling 20 students. The data collection technique in this study used a multiple choice test instrument totaling 25 items. Based on the results of research conducted at MI Nurul Falah Karangpuri, it was found that the average student learning outcomes during the pretest in class IV were 65, while the student learning outcomes during the posttest were 78. As evidenced by the t test results of 11.376 with a significance value of 5%, it is concluded that there is an effect of the guided inquiry learning model because t count is greater than t table, namely 11.376> 2.093 then Ha is accepted and Ho is rejected. Thus, the Guided Inquiry Model affects the learning outcomes of grade IV students at MI Nurul Falah Karangpuri.